Qualification of the public transport offer in relation to spatial coverage Case of the city of Guelma - Bennacer, Leila; Benmechiche, Meriem; Abdelouheb, Fadel (Journal of Human Sciences, 2021)
The city of Guelma like all Algerian cities, has a remarkable urban sprawl reached 15.53 km2 during the period from 1985 to 2021. This urban growth due to an increase in the population which reached 187,000 inhabitants in 2015, which generates displacements which are carried out by public transport. Our objective is to qualify the supply of public transport by bus and minibus, as well as their spatial coverage, which required an importance in regional planning. However, the presentation of the spatial coverage of collective urban transport lines, and whether the entire population and areas of the city are served by these lines. The service to the different neighborhoods, by representing it in the form of maps from satellite images with ribbons of 300 and 500 m, which will make it possible to assess the areas served and the areas not served, as well as the fairness of the distribution spatial distribution of the various public transport lines.